Long queue estimation for signalized intersections using mobile data. (December 2015) - Hao, Peng; Ban, Xuegang
Highlights: Short vehicle trajectories are collected and used from mobile sensors. Missing acceleration/deceleration process is estimated from short vehicle trajectories. Models are trained using sample short vehicle trajectories from multiple cycles. The queue profile and maximum queue length of a cycle can be estimated. Abstract: Queue length is one of the key measures in assessing arterial performances. Under heavy congestion, queues are difficult to estimate from either fixed-location sensors (such as loop detectors) or mobile sensors since they may exceed the region of detection, which is defined as long queue in the literature. While the long queue problem has been successfully addressed in the past using fixed-location sensors, whether this can be done using mobile traffic sensors remains unclear. In this paper, a queue length estimation method is proposed to solve this long queue problem using short vehicle trajectories obtained from mobile sensors. The method contains vehicle trajectory reconstruction models to estimate the missing deceleration or acceleration process of a vehicle. Long queue estimation models are then developed using the reconstructed vehicle trajectories. The proposed method can provide estimates of the queue profile and the maximum queue length of a cycle. The method is tested in a field experiment with reasonable results.